PERANCANGAN PROGRAM APLIKASI MANAJEMEN KOLEKSI MUSEUM BAHARI BERBASIS WEBSITE - Ilona, Valencia; Wasino, Wasino; Tony, Tony (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
Maritime museum is a museum for keeping and displaying the collection of history objects that related to the nautical Indonesian people. The purpose of this application program design is to assist maritime museum personnel in making data collection, computing revenue of ticket selling and events, assisting to introduce maritime museum for public. There are some modules in this design like login, forgot password, home, collection, information, visiting, about us, comment, collection input, account, advertisement, searching collection, site map, price and transaction input, transaction list, report, and logout. The collection management design of maritime museum through a web-based uses not only waterfall methodology, but supporting equipments as well which are Microsoft Word for making a report, Microsoft Visio for making a flowchart, DFD (Data Flow Diagram), ERD (Entity Relationship Diagram), interrelated table, system dialogue design. Others like PHP, HTML programming language, and MySQL database. The collection management website of maritime museum has been tested using white box and black box testing method. The results of the existence of collection management website of maritime museum is able to assist the museum personnel in making a collection report, computing revenue of ticket selling and events, assisting to introduce maritime museum for public.